Evaluation of TNF-alpha, IL-4, and IL-10 and parasite density in spleen and liver of L. (L.) chagasi naturally infected dogs - Michelin, A. de F. [UNESP]; Perri, Silvia Helena Venturoli [UNESP]; Lima, Valéria Marçal Felix de [UNESP] (Maney Publishing, 2011)
Dogs are the main domestic reservoirs of L. (L.) chagasi. Once in the vertebrate host, the parasite can cause visceral leishmaniasis, which can also be transmitted to humans. Cytokines are key elements of the host immune response against Leishmania spp. To investigate whether tumor necrosis factor (TNF)-alpha, interleukin (IL)-4 and IL-10 are associated with pattern infection in dogs, these cytokines were quantified in the spleen and liver of dogs naturally infected with L. (L.) chagasi, with or without clinical manifestations, and their levels were correlated with the parasite load verified in these organs. A total of 40 adult dogs naturally infected with L. (L.) chagasi were assessed, together with 12 uninfected control dogs. Samples from spleen and liver were used to determine the cytokine levels by capture ELISA and for quantifying parasite load by real-time PCR. Statistical analysis was performed using the minimum Chi square method and group means were compared using the Tukey test. TNF-alpha, IL-4 and IL-10 levels in infected dogs were higher than in control groups; the liver was the main cytokine-producing organ during infection. The level of splenic TNF-alpha showed correlation with parasite load and may represent an important marker for infection process evolution, with the participation of IL-10. These results may contribute to a clearer understanding of the immune response in dogs infected with L. (L.) chagasi, which may lead to the development of prophylactic or preventive measures for these animals.